Peran Kinerja Keryawan Dalam Meningkatkan Pelayanan Rekam Medis pada Klinik Mitra Medika - Zailani, Zaini Rahmat; Adji, Wilma Zuarko (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
In every company or organization, employee performance is an important part of improving service and progress of a company. The research was conducted at Mitra Medika Clinic. The population in this study was 245 with a sample taken of 152 respondents. This study aims to determine the role of employee performance in improving medical record services at Mitra Medika Clinic. The analytical method used in this research is simple linear regression. The results showed that the role of employee performance had a positive and significant effect on improving medical records at Mitra Medika Clinic. Keywords: performance, service